Transaction Costs And Export Intensification – The Cases Of Poland And Hungary - Mroczek-Dąbrowska, Katarzyna (Comparative Economic Research. Central and Eastern Europe, 2016)
The purpose of this paper is to explain if and how foreign sales are affected by the level of transaction costs within industries in Poland and Hungary. The main hypotheses reflect the potential correlation for different types of industries. The paper attempts to transfer the notion of transaction costs, originally applied at the micro-perspective level, to the analysis of industries using a mesoeconomic perspective. We argue that transactions cost levels influence the overall willingness to expand abroad. While there has been much research carried out in the area of export intensification of particular companies, few empirical studies can be found concerning entire industries.